STUDY ON IN-SERVICE INSPECTION PROGRAM AND METHOD FOR FUEL HANDLING SYSTEM OF RDE - Alim Mardhi; Andryansyah Andryansyah; Mudi Haryanto; Topan Setiadipura; Ari Nugroho (Indonesian Journal of Engineering and Science (IJES), 2021)
One of the main programs that should be established on the designing process of the fuel handling system is to establish an in-service inspection program for maintaining the integrity of the system, structure and component during service lifetime. The most important role of in-service inspection is the nondestructive examination techniques. The objective of this study is to propose a preliminary program for examining the integrity of the fuel handling system during operation and determining the best method to confirm the defects. The proposed programs are described as follows, defining the operating environment of the fuel handling system, identifying the material characteristics during operation which indicates to promote the defects, and selecting the appropriate method of non-destructive examination and analysis technique for such kind of defects. The proposed in-service inspection program is expected to give significant additional value to the fuel handling system design of RDE.